Pelatihan Administrasi Keuangan Organisasi Himpunan Mahasiswa Program Studi Ahwal Al-Syakhshiyah Universitas Muhammadiyah Buton - Azaluddin Azaluddin; Syamsul Bahri Bahar; Abdul Rahim (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2022)
The financial planning of the Ahwal Al-Syakhshiyah Study Program Student Association at the Muhammadiyah University of Buton must be carried out through financial administration. Financial planning takes into account a number of variables, including projected sales, pro forma reports, asset requirements, economic assumptions, and how investments are financed. Budgeting, spending, and saving for the future can all be done through financial planning. The method of activity used is the method of lectures, discussions, questions and answers, assignments, practice and training. The results of this dedication show that the Pre-test understanding of organizational financial administration found that 1 student (14.28%) got the very low category, 2 students (28.57%) got the low category, and 4 students (57.14%) got the moderate, and there was an increase after the Post-test on understanding organizational financial administration found that 2 students (28.57%) got the medium category, 4 students (57.14%) got the high category, and 1 student (14.29%) got very high category. This means that the implementation of this activity can improve and develop the organizational financial administration of the Ahwal Al-Syakhshiyah Study Program Student Association, Muhammadiyah University of Buton.